2022
DOI: 10.3390/app12031359
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant and Wound Healing Potential of Three Artemisia Species: In Vitro and In Ovo Evaluation

Abstract: Skin injuries, and especially wounds of chronic nature, can cause a major negative impact on the quality of life. New efficient alternatives are needed for wound healing therapy and herbal products are being investigated due to a high content of natural compounds with promising healing activity. For this purpose, we investigated three Artemisia species, Artemisia absinthium L. (AAb), Artemisia dracunculus L. (ADr) and Artemisia annua L. (AAn). Ethanolic extracts, containing different polyphenolic compounds, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…The A. abrotanum polyphenolic compound-rich extract had higher quantities of rutin (10.57 µg/mL), umbelliferone (17.03 µg/mL), and chlorogenic acid (103.47 µg/mL), while S. officinale polyphenolic compound-rich extract had higher quantities of caffeic acid (9.42 µg/mL), ellagic acid (43.79 µg/mL), and rosmarinic acid (136.140 µg/mL). As shown in other studies, chlorogenic acid and rutin have also been identified as major constituents in Artemisia ethanolic extract from other species [ 40 , 41 ]. Although there are few studies on the polyphenolic compounds profile of S. officinale extracts, rosmarinic and caffeic acid were also found to be major polyphenols by Sowa et al [ 42 ], Trifan et al [ 43 ], and the presence of caffeic acid was also reported by Nastić et al [ 44 ].…”
Section: Resultsmentioning
confidence: 59%
“…The A. abrotanum polyphenolic compound-rich extract had higher quantities of rutin (10.57 µg/mL), umbelliferone (17.03 µg/mL), and chlorogenic acid (103.47 µg/mL), while S. officinale polyphenolic compound-rich extract had higher quantities of caffeic acid (9.42 µg/mL), ellagic acid (43.79 µg/mL), and rosmarinic acid (136.140 µg/mL). As shown in other studies, chlorogenic acid and rutin have also been identified as major constituents in Artemisia ethanolic extract from other species [ 40 , 41 ]. Although there are few studies on the polyphenolic compounds profile of S. officinale extracts, rosmarinic and caffeic acid were also found to be major polyphenols by Sowa et al [ 42 ], Trifan et al [ 43 ], and the presence of caffeic acid was also reported by Nastić et al [ 44 ].…”
Section: Resultsmentioning
confidence: 59%
“…Interestingly, the data also suggested the bactericidal potential of AAE against MRSA, as a 21 mm zone of inhibition ( Figure 2 C and Table 1 ) was found, and more than 90% of the cells ( Figure 2 C) were dead when treated with 6 mg/mL. Earlier, some studies reported the efficacy of A. turanica and A. dracunculus against MRSA in vitro and in vivo respectively [ 51 , 52 ]. Previous studies suggested the antimicrobial potential of plant extracts against MRSA due to the presence of the compounds having β-lactamase inhibiting properties [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 63%
“…Previous study on A. biennis Willd, showed that, the hydroethanolic extract of the plant had the highest amount of phenolic content and antioxidant activity 31 . Another research on A. absinthium demonstrated that the ethanolic extract had more TPC than A. dracunculus and A. annua 32 . In another study, among six Artemisia species, A. oliveriana had the highest TPC and A. diffusa had the highest TFC 33 .…”
Section: Resultsmentioning
confidence: 98%